Analysing the factors affecting implementation and cost analysis of biodigester systems: toward sustainable waste management solutions / Firas Qistina Mohd Razlan, Ani Saifuza Abd Shukor and Saipol Bari Abd Karim - Mohd Razlan, Firas Qistina; Abd Shukor, Ani Saifuza; Abd Karim, Saipol Bari (UiTM Press, 2024)
Biodigester systems have recently drawn attention as an innovative and long-term solution to food waste since they use organic waste to produce biogas and bio-fertilisers rather than dump food waste in landfills. Food waste is a worldwide problem that negatively impacts on the environment, society, and economy. Therefore, implementing a biodigester system will reduce food waste issues. The conversion of food waste to biogas has high potential as a sustainable waste management solution. This study aims to establish a deeper understanding of implementing a biodigester system by identifying the factors to consider when implementing a biodigester system and analysing the associated costs. This study utilises three case studies of three (3) biodigester systems in Klang Valley that three (3) local authorities have implemented, as well as semistructured interviews with assistant directors from the local authorities. As for the outcome, the feedstock supply is the factor to consider when implementing a biodigester system, and its cost ranges from RM 200,000.00 to RM 450,000.00. The output of the study can be deployed as a lead to boost its implementation and improvement in the future.